Kahoot in Arabic Language Learning: A Qualitative Study of Implementation and Student Perceptions at Al Azhar Pare Institute - Ahmad Nafis; Ahmad Tajuddin; Parmansyah Parmansyah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to explore the implementation of the Kahoot application in Arabic language learning at the Al Azhar Pare Institute and to analyze participants' perceptions of its use. Employing a descriptive qualitative approach, primary data were collected through open-ended questionnaires distributed to 25 basic-level course participants. Data analysis employed thematic analysis techniques following the Braun Clarke model. The findings reveal three central themes: (1) Kahoot as a catalyst for motivation and a reducer of learning monotony, (2) its effectiveness as a medium for reinforcing vocabulary and fundamental grammatical structures, and (3) technical constraints and suggestions for future development. Participants reported that the learning atmosphere became significantly more interactive, enjoyable, and fostered healthy competition, which enhanced their engagement. The immediate feedback provided by the application was also highlighted as beneficial for consolidating their understanding of the material. However, challenges related to unstable internet connectivity and the need for more contextually relevant quiz content were identified. The study concludes that Kahoot serves as a powerful supportive tool for creating a dynamic and participatory Arabic learning environment in non-formal educational settings. It is recommended that instructors integrate Kahoot more systematically into lesson plans and develop quiz content that aligns closely with learners' communicative needs to maximize its pedagogical potential.